Actor role of comparative foreign presence in regional autonomy: The case of Aceh, Mindanoa and Southern Thailand - Nellis Mardhiah (Proceedings of AICS - Social Sciences, 2013)
Actor role abroad is not rational actors but devotees pluralist international organizations. Foreign policy is the result of disputes, bargaining, and compromise between many different actors. Foreign policy of the recruitment process is not rational process but a social process. It is the process to change the position and the results of overseas conflicts actor was referring to the difficult issues resolved, especially involving the values #8203;#8203;of life. Consultation undertaken will produce a compromise on both sides especially the things that divided equally. This study analyzes documentation from previous studies. The three issues are very complex in the approach by the respective governments have played is the same solidarities. Possible policy approaches in Aceh as a national issue from the old order to the new order did not work in peace. But with the success HDC mediators autonomous region status. Mindanao is also the case when the open dialogue supported by ASEAN through OKI mediators to achieve ARMM with the MNLF and the Philippine government bring. While in Southern Thailand is done with a variety of approaches and thus more complicated question, and the Government of Thailand Thailand is considered as a national issue in the case of the Southern Thailand Pattani political approach that uses the theory of conflict management and conflict termination will peel intention behind these approaches conflict resolution has been carried out Pattani, Narathiwat and Yala this. Through the analysis, there might be things that are not clear in the case of trying to hide this particular role played by the Thai government in addressing the issues that arise, so that the proposed autonomous region was still in the of process.Keywords: Actor Role of Foreign Affairs, Regional Autonomy